Strategi Menghilangkan Fobia Air: Sebuah Pendekatan menuju Keamanan Pembelajaran Akuatik - Ermawan Susanto (Jurnal Pendidikan Jasmani Indonesia, 2005)
Water phobia is a kind of resisting factors in doing the aquatic study. Excessivefear is very disturbing for acquiring the skill of swimming. Swimming which ought to beeasy to be learned by man of all ages will mean nothing if the water phobia be still inmind. The problem is how to eliminate the excessive fear of water, so that somebodymay reach his optimal potency in mastering the aquatic skill.Strategy of eliminating the water phobia is an approach for optimizing the aquatic study.This strategy is expected to become an instrument which can assist physical educationteachers, all instructors or practitioners of swimming to overcome the problem of thewater phobia. Its trouble-shooting efforts apply the approach and the environment’sfacilitation which are emotionally, mentally, and physically supporting the course of thestudy. The water phobia can be caused by genetic elements. It can also be caused byeffects of a traumatic experience with water. The water phobia is also happened by theeffect of having cold feet posed by parents or adults. Peculiarly this strategy is addressedfor those who have fear or feel unsafe around or under water, both for children and alsoadults.Implications of this strategy affect the disappearance of excessive fear of water, andthen encourage the self confidence to perform the aquatic activity. Through physicaleducation teachers, swimming instructors, mental health experts, parents, and adults,the problem of those who suffer from the water phobia can be minimized.Keyword: Strategy, The Water Phobia, The Aquatic Activity, Physical Education